2015
DOI: 10.2147/jhc.s81309
|View full text |Cite
|
Sign up to set email alerts
|

Type I insulin-like growth factor as a liver reserve assessment tool in hepatocellular carcinoma

Abstract: Chronic liver diseases (CLDs) encompass a wide range of illnesses, including nonalcoholic fatty liver disease, nonalcoholic steatohepatitis, and viral hepatitis. Deterioration of liver capacity, with subsequent progression into cirrhosis and hepatocellular carcinoma (HCC), ultimately leads to a further decrease in the hepatic reserve. The Child–Turcotte–Pugh scoring system is the standard tool for assessing underlying liver reserve capacity in routine practice and in clinical trials of CLD and HCC. In this rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 146 publications
2
11
0
Order By: Relevance
“…Most likely, these findings can be attributed to the fact that treatment with DEN, with or without PLE, produces substantial liver necrosis with progressive fibrosis and cirrhosis; thus, decreased IGF1 levels correlated with decreased functional capacity of the liver in the DEN-treated pigs. We expected that, as IGF1 levels decreased, GH levels would increase because of the negative feedback effects of the decreased IGF1 levels on the pituitary gland, similar to recent observations reported by our group [30]. Our current study, however, did not demonstrate a negative correlation between GH and IGF1.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Most likely, these findings can be attributed to the fact that treatment with DEN, with or without PLE, produces substantial liver necrosis with progressive fibrosis and cirrhosis; thus, decreased IGF1 levels correlated with decreased functional capacity of the liver in the DEN-treated pigs. We expected that, as IGF1 levels decreased, GH levels would increase because of the negative feedback effects of the decreased IGF1 levels on the pituitary gland, similar to recent observations reported by our group [30]. Our current study, however, did not demonstrate a negative correlation between GH and IGF1.…”
Section: Discussionsupporting
confidence: 89%
“…For instance, recent findings from our group suggest that the GHR/IGF1 signaling axis plays an important role in HCC [30]. In our current study, the expression of GHR and IGF1R was very pronounced in the HCC tissue from DEN-treated pigs.…”
Section: Discussionsupporting
confidence: 53%
“…Some case–control studies have supported a positive association between the insulin-like growth factor-1 (IGFI) level and the risk of liver cancer [ 2 4 ]. Indeed, in clinical practice, IGFI is used to assess HCC reserve capacity [ 5 , 6 ] and as a prognostic marker for HCC progression and survival [ 3 ]. However, further research is needed.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, serum IGF-1 levels varied in patients based on their CTP classes. Cirrhotic patients with preserved liver functions defined as CTP class A tended to have higher IGF-1 levels than patients with advanced-stage CTP class B and C. 11 , 33 Therefore, serum IGF-1 has been considered as a surrogate marker for hepatic reserve in cirrhotic patients. Consistent with these findings, we found that IGF-1 levels changed significantly according to the presence or absence of cirrhosis of the patients in our study, Table 5 .…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between IGF-1 level and hepatic function has been reported by several studies that demonstrated the correlation between the severity of cirrhosis and the development of HCC and low serum IGF-1 concentration. 11 13 Furthermore, the levels of IGF-1 are significantly lower in patients with cirrhosis CTP C than CTP A and B. Additionally, correlation with other advanced cirrhotic and portal hypertension parameters such as albumin level, INR value, and spleen size also has been reported. 14 – 16 Similarly, a significant decrease in IGF-1 concentration was observed in patients with advanced HCC.…”
Section: Introductionmentioning
confidence: 95%